Removal of Endobronchial Malignant Mass by Cryotherapy Improved Performance Status to Receive Chemotherapy. (14th October 2014) - Fang, Yueh-Fu; Hsieh, Meng-Heng; Wang, Tsai-Yu; Lin, Horng-Chyuan; Yu, Chih-Teng; Chou, Chun-Liang; Lin, Shu-Min; Kuo, Chih-Hsi; Chung, Fu-Tsai
Abstract : Although malignant endobronchial mass (MEM) has poor prognosis, cryotherapy is reportedly a palliative treatment. Clinical data on postcryotherapy MEM patients in a university-affiliated hospital between 2007 and 2011 were evaluated. Survival curve with or without postcryotherapy chemotherapy and performance status (PS) improvement of these subjects were analyzed using the Kaplan-Meier method. There were 59 patients (42 males), with median age of 64 years (range, 51–76, and median performance status of 2 (interquartile range [IQR], 2-3). Postcryotherapy complications included minor bleeding (n = 12 ) and need for multiple procedures (n = 10 ), while outcomes were relief of symptoms (n = 51 ), improved PS (n = 45 ), and ability to receive chemotherapy (n = 40 ). The survival of patients with chemotherapy postcryotherapy was longer than that of patients without such chemotherapy (median, 534 versus 106 days; log-rank test, P = 0.007 ; hazard ratio, 0.25; 95% confidence interval, 0.10–0.69). The survival of patients with PS improvement postcryotherapy was longer than that of patients without PS improvement (median, 406 versus 106 days; log-rank test, P = 0.02 ; hazard ratio, 0.28; 95% confidence interval, 0.10–0.81). Cryotherapy is a feasible treatment for MEM. With better PS after cryotherapy, further chemotherapy becomes possible for patients to improve survival when MEM caused dyspnea and poor PS.